Preparing pharmacy students to communicate effectively with adolescents. (1st October 2019) - Gilmartin-Thomas, Julia F M; Sleath, Betsy; Cooper Bailey, Stacy; Carpenter, Delesha M; Chater, Angel; MacAllister, Catherine; Pyzik, Oksana; Wayman, Brandi; Annis, Izabela E; Smith, Felicity
Abstract: Objectives: To develop an elective workshop designed to equip pharmacy students with skills to effectively communicate with adolescents. To conduct preliminary evaluation of the workshop to assess its impact on pharmacy student perceived confidence and knowledge relating to the importance of adolescent counselling and counselling techniques. Methods: Academics from three universities in three countries collaborated on the workshop development and evaluation. The workshop structure was designed upon the foundations of communication best practices and established techniques, and it consisted of two online modules and an in-person tutorial. Pharmacy students undertaking a 4-year Bachelor, Master or Doctor of Pharmacy degree from all three participating universities evaluated the workshop via pre- and post-questionnaires. Key findings: A total of 81 pharmacy students volunteered to attend and evaluate the workshop. Of these 81 students, 31 completed paired pre- and post-questionnaires, 44 students completed unpaired questionnaires and six students were lost to follow-up. Of the paired pre- and post-questionnaires, students were mostly female (67.7%) with an average age of 24.9 years (standard deviation, SD = 5.6) and were in the first (32.3%), second (16.1%) or third (51.6%) year of their pharmacy programme. Over 80% of students somewhat or strongly agreed that the workshop made them feel more comfortable speaking with young people in pharmacy settings. Mean (SD) perceived confidence (pre = 21.7 (4.0) and post = 24.9 (4.5)) and knowledge scores (pre = 5.2 (1.5) and post = 6.6 (1.6)) significantly improved after undertaking the workshop. Conclusions: The workshop increased pharmacy student perceived confidence and knowledge relating to the importance of adolescent counselling and counselling techniques.